Optimal Leverage and Aggregate Investment - Biais, Bruno; Casamatta, Catherine (Journal of Finance, 1999)
We analyze the optimal financing of investment projects when managers must exert unobservable effort and can also switch to less profitable riskier ventures. Optimal financial contracts can be implemented by a combination of debt and equity when the risk‐shifting problem is the most severe while stock options are also needed when the effort problem is the most severe. Worsening of the moral hazard problems leads to decreases in investment and output at the macroeconomic level. Moreover, aggregate leverage decreases with the risk‐shifting problem and increases with the effort problem.